Bibliometric Insights into Green Finance and Economic Development: Global Trends and Collaborations - Gupta, Jagriti; Singh, Avadhesh; Jyoti, Jyoti; Verma, Dewansh; Mishra, Akhil (International Journal of Energy Economics and Policy, 2025)
Green finance has emerged as a prominent developmental trend in the financial sector, owing to its growing worldwide significance. It has become common practice to address both concerns at once by combining environmental conservation measures with economic growth. But whether green finance can effectively tackle the global economic problems of today is still up for debate. The goal of this study was to identify understudied regions of the world by examining publication patterns in the literature on green finance and economic growth. The study attempted to identify trends in green finance and economic development research publications across nations, continents, contributing authors, and journals. 289 publications that were taken from the Scopus database were used in this bibliometric analysis. The study used a bibliometric technique using R Studio software. The study identifies the most prolific and noteworthy authors, articles, and related publications. Specifically, co-citations and collaboration analysis allowed for the mapping of the most current and oldest research fronts. With a disparate quantitative production of scientific literature among nations and organizations, this field of study is still relatively young. As a means of promoting research in the field of green finance and economic development, this study painted a picture of an emergent, multidisciplinary sector that may be of interest to all stakeholders dealing with similar problems. The findings offer solid recommendations for more research in this area.